THE RESULTS OF THE TECHNICAL INSPECTION OF THE REINFORCED CONCRETE BRIDGE ACROSS THE DESNA RIVER AT KM. 23+400 OF THE HIGHWAY IN THE CITY OF TURBIV - Burchenia , С.; Vikhot , С.; Gayda , О. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2024)
There are many reasons that can lead to the deterioration of the technical condition of buildings and structures. The main ones include: a change in the seismic resistance of the site as a result of the approved norms in Ukraine, an increase in the load on the load-bearing structures, physical aging of the construction materials during intensive and long-term operation, the aggressive effect of the temperature and humidity parameters of the environment on concrete and reinforcement, the occurrence of unforeseen in the project vibration loads that can lead to an emergency technical condition of structures, etc. A timely inspection and determination of the technical condition of the object as a whole will allow to determine the possibility of further operation or the need to restore structural elements, by changing calculation schemes, finding new methods for calculating the stress-strain state, forecasting the service life, applying new technological solutions and materials in the design and strengthening of buildings and structures. Assessment and forecasting of the technical condition of the bridge and its elements is determined on the basis of inspection and observation data, survey results and verification calculations. Therefore, it is extremely important not only to determine the operational condition, but also to determine the coefficient of the structural reserve. The article presents the results of the technical condition of the bridge as a whole and its elements in particular, built more than 55 years ago. Defects and damage that occurred during its operation were detected. As a result of the survey work, it was found that during the construction process and during long-term operation, under the influence of aggressive factors of the external environment and motor vehicles, defects and damage accumulated in individual elements of the structures over time, which reduced the operational indicators, reliability and durability of the bridge and negatively affected the safety and comfort of movement. The generalized characteristic of the state indicates that a partial violation of the requirements of the first group of boundary conditions is possible, and the requirements of the second group of boundary conditions are violated. The building is operated in a limited mode and requires special control over the state of its elements. In order to ensure the normal operation of the bridge, it is necessary to carry out major repairs of the structure with the restoration of the proper operational condition of the structure.